Sex-differential effect of waist circumference on new-onset cerebral infarction: a nationwide cohort study - Lee, Sang Min; Hong, Minha; Ryoo, Jae-Hong (Frontiers in Neurology, 2024)
Introduction Excessive abdominal adiposity represents a cardiovascular disease risk factor. Waist circumference (WC) reflects abdominal adiposity and is known as an easy-to-measure indicator of obesity. This study aimed to evaluate the relationship between WC level and the development of cerebral infarction in Koreans. Methods 209,442 Koreans were included among the general population registered in the National Health Information Database. Depending on the degree of WC, the possibility of cerebral infarction was tracked for 4.37 person-years. Identification of patients with cerebral infarction was confirmed through the diagnostic code ICD I63 of inpatient or outpatient. Participants’ data were analyzed by sex. The hazard ratios (HRs) and confidence interval (CI) for cerebral infarction were calculated using the Cox proportional hazards model. Results and discussion Between 2009 and 2013, 2,403 cases (1.15%) of cerebral infarction occurred during the follow-up period of 915,223.6 person-years. The HRs (95% CI) for incident cerebral infarction in men was adjusted for multiple covariates, and comparison of WC levels second, third, and fourth quartile with the first quartile showed 1.10 (0.94–1.28), 1.11 (0.95–1.30), and 1.24 (1.07–1.45), respectively (P for trend 0.045). This association was not significant in women (P for trend 0.619). The severity of WC levels in men is significantly associated with the risk of developing cerebral infarction in Koreans. This finding indicates that other measurements for excessive adipose visceral tissue, except abdominal circumference, need to be taken into account to identify the risk of cerebral infarction in women.